The fourth industrial revolution and the coronavirus: A new era catalyzed by a virus (2020)
The global pandemic caused by the new coronavirus, COVID 19, has disrupted the lives of most people on the planet. The magnitude of such disruption can only be compared to those caused by World War II. Experts suggest that in order to better evaluate this situation, it should be divided into two waves. The first wave being associated with health issues and the second one with economic issues. This article suggests that this global pandemic is fostering yet a third wave, which in the long run can be much more impactful in our lives than the first two. This third wave consists on accelerating the implantation process of the fourth industrial revolution. This article is divided into sections with the physical, digital and biological spheres of the fourth industrial revolution, as well as the dimensions of sustainability and other important considerations, in order to better demonstrate the emergence of a new era catalyzed by a virus.